2018
DOI: 10.29399/npa.22997
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish Version of Pain Assessment in Advanced Dementia (PAINAD) Scale

Abstract: The PAINAD-TR scale can be used for the assessment and management of pain in non-communicative older adults with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…32 Regarding the degree of agreement among observers, the ICC values of this version (0.94) are higher than those found by the Chinese version (0.84) 32 and the Turkish version (0.81). 36 Finally, regarding temporary stability, the findings of this study have shown a moderate reliability of the PAINAD scale in its Spanish version, since the ICC is 0.55. This has been lower than other versions, since the ICC of the Chinese version ranges from 0.80 to 0.86, 32 the ICC of the Turkish version is 0.81, 36 the ICC of the German version is 0.80 37 and the ICC of the Italian version is 0.88.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…32 Regarding the degree of agreement among observers, the ICC values of this version (0.94) are higher than those found by the Chinese version (0.84) 32 and the Turkish version (0.81). 36 Finally, regarding temporary stability, the findings of this study have shown a moderate reliability of the PAINAD scale in its Spanish version, since the ICC is 0.55. This has been lower than other versions, since the ICC of the Chinese version ranges from 0.80 to 0.86, 32 the ICC of the Turkish version is 0.81, 36 the ICC of the German version is 0.80 37 and the ICC of the Italian version is 0.88.…”
Section: Discussionmentioning
confidence: 62%
“…36 Finally, regarding temporary stability, the findings of this study have shown a moderate reliability of the PAINAD scale in its Spanish version, since the ICC is 0.55. This has been lower than other versions, since the ICC of the Chinese version ranges from 0.80 to 0.86, 32 the ICC of the Turkish version is 0.81, 36 the ICC of the German version is 0.80 37 and the ICC of the Italian version is 0.88. 31 This difference could be explained because the retest was performed after a shorter time interval 31 32 in other studies, such as in the German version, 37 which performed both the test and the retest on the same day.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Multiple prior studies have also provided support for the reliability and validity of the PAINAD when used with the multiple ethnicities (49,50) and across many clinical conditions (11,13,14,51,52). These studies did not, however, compare use across the Black vs. White older adults and did not use a Rasch analysis approach.…”
Section: Discussionmentioning
confidence: 89%